2013
DOI: 10.1523/jneurosci.2949-12.2013
|View full text |Cite
|
Sign up to set email alerts
|

A Corticotropin Releasing Factor Pathway for Ethanol Regulation of the Ventral Tegmental Area in the Bed Nucleus of the Stria Terminalis

Abstract: A growing literature suggests that catecholamines and corticotropin releasing factor (CRF) interact in a serial manner to activate the bed nucleus of the stria terminalis (BNST) in order to drive stress- or cue-induced drug- and alcohol-seeking behaviors. Data suggests that these behaviors are driven in part by BNST projections to the ventral tegmental area (VTA). Together these findings suggest the existence of a CRF-signaling pathway within the BNST that is engaged by catecholamines and regulates the activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
182
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(194 citation statements)
references
References 46 publications
(80 reference statements)
10
182
1
1
Order By: Relevance
“…Koob and Volkow (2010) provide a comprehensive model of addiction neurobiology that proposes distinct neural circuits for three stages of addiction: binge/intoxication; withdrawal/negative affect; and preoccupation/craving addiction (also see Koob and Moal, 1997). In the Koob and Volkow model, the BNST has a prominent role in the withdrawal/negative affect stage of addiction, consistent with evidence that highlights the role of BNST in withdrawal across drugs of abuse, including alcohol (Silberman et al, 2013;Wills et al, 2012) and opiates (Wang et al, 2006;Delfs et al, 2000). The withdrawal/negative affect stage has been described as the 'dark side of addiction' and includes core components of anxiety disorders.…”
Section: An Emerging Role For the Bnst In Addictionmentioning
confidence: 64%
See 1 more Smart Citation
“…Koob and Volkow (2010) provide a comprehensive model of addiction neurobiology that proposes distinct neural circuits for three stages of addiction: binge/intoxication; withdrawal/negative affect; and preoccupation/craving addiction (also see Koob and Moal, 1997). In the Koob and Volkow model, the BNST has a prominent role in the withdrawal/negative affect stage of addiction, consistent with evidence that highlights the role of BNST in withdrawal across drugs of abuse, including alcohol (Silberman et al, 2013;Wills et al, 2012) and opiates (Wang et al, 2006;Delfs et al, 2000). The withdrawal/negative affect stage has been described as the 'dark side of addiction' and includes core components of anxiety disorders.…”
Section: An Emerging Role For the Bnst In Addictionmentioning
confidence: 64%
“…Emerging evidence suggests that a tiny region in the ventral forebrain-the bed nucleus of the stria terminalis (BNST)-is a critical node in the stress response neurocircuitry and may play a significant role in both anxiety and addiction, two highly prevalent and debilitating stress-related disorders. Rodent studies of the BNST over the past two decades have led to exciting discoveries about its potential role in human psychopathology-seminal studies have shown a unique role for the BNST in contextual fear and sustained, anxiety-like responses in rodents (see, eg, Davis et al, 2010;Walker et al, 2003), and parallel work in drug addiction demonstrates the role of BNST in withdrawal related-anxiety and relapse (Buffalari and See, 2011;Silberman et al, 2013;Wenzel et al, 2014). Although anxiety and addiction are often considered to have distinct neurobiological bases-anxiety related to fear neurocircuitry and addiction related to reward circuitry-we now understand the two disorders also have many commonalities; for example, anxiety and addiction are both triggered by stress (Koob, 2009;McEwen, 2012), risk for both disorders is heightened in individuals with altered stress reactivity (Lovallo, 2006;Villada et al, 2014), and the two disorders are highly comorbid (Grant et al, 2004;Kessler et al, 2005b).…”
Section: Introductionmentioning
confidence: 99%
“…The BNST, which contains a high density of RXFP3 (19,21), has an established role in stress-induced reinstatement via a CRF-signaling pathway (41,43) and therefore was an obvious candidate region for targeted injections of R3(B1-22)R. Accordingly, intra-BNST injections of R3(B1-22)R produced a significant decrease in both alcohol selfadministration and stress (yohimbine)-induced reinstatement of alcohol-seeking. The attenuation of alcohol-seeking, rather than complete prevention, suggests other brain regions may also be involved.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, most electrophysiological studies have focused on other aspects of BNST physiology such as the influence of various peptides/transmitters (Grueter et al 2005;Krawczyk et al 2011a;Li et al 2012;Lungwitz et al 2012;McElligott and Winder 2008;Nobis et al 2011;Puente et al 2010;Shields et al 2009), particularly corticotropin releasing factor (Gafford et al 2012;Ide et al 2013;Kash and Winder 2006;Oberlander and Henderson 2012;Silberman et al 2013), mechanisms of addiction and relapse to drug seeking (Conrad et al 2012;Davis et al 2008;Dumont and Williams 2004;Dumont et al 2005Dumont et al , 2008Grueter et al 2008;Kash et al 2008aKash et al ,b, 2009Krawczyk et al 2011b), synaptic plasticity (Weitlauf et al 2005), and the impact of stress (Conrad et al 2011).…”
Section: Prior Studies On the Physiology Of Bnst-a Neuronsmentioning
confidence: 99%